Penerapan Model Drill and Practice untuk Meningkatkan Kemampuan Berpikir Analitis pada Pembelajaran Matematika - Muhammad Irhamuddin; Ahmad Muslih; Khalimatul Hidayah; Naila Faizatur Rohmah; Muhammad Syarifudin; Suyadi Suyadi (Kampus Akademik Publiser, 2025)
Student engagement in the learning process is significantly influenced by the strategies implemented by teachers. Students' learning activities not only reflect their understanding of the material but also indicate their motivation and interest, which are shaped by a supportive learning environment. One instructional model that can foster active learning is the Differentiated Instruction model. The purpose of this study is to describe the steps, strengths, and weaknesses of implementing the Differentiated Instruction model in Islamic Education (PAI) learning at Madrasah Aliyah Negeri 2 Rembang, Madrasah Tsanawiyah Negeri 4 Klaten and Madrasah Aliyah Negeri Sukoharjo. This research employs a qualitative approach. The research subjects are teachers at Madrasah Aliyah Negeri 2 Rembang, Madrasah Tsanawiyah Negeri 4 Klaten and Madrasah Aliyah Negeri Sukoharjo, with Islamic Education teachers serving as the informants. Data collection techniques include interviews, observations, and documentation. The findings of this study are: (1) The steps of the Differentiated Instruction model include identifying student needs, grouping students, designing flexible learning activities, utilizing technology, employing diverse assessments, and evaluating understanding and internalization of values through questioning or assignments; (2) The advantages of the Differentiated Instruction model include enhanced material comprehension, appreciation of student diversity, avoidance of labeling students as weak or smart, and increased motivation and interest in learning; (3) The weaknesses of the Differentiated Instruction model involve time and resource limitations, teacher readiness, and limited facilities. The conclusion of this study is that the Differentiated Instruction model can be applied in the learning process as an effort to improve student engagement during the learning process at the Madrasah level.